1996
DOI: 10.1159/000139362
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Superoxide Dismutase from Ascaris suum by Benzimidazoles and Synthesized Pyrimidine and Glycine Derivatives

Abstract: Copper-zinc superoxide dismutase was purified from Ascαris suum (Nematoda). Four benzimidazole derivatives, six recently synthesized pyrimidine derivatives and eleven recently synthesized glycine derivatives were shown to inhibit: (1) purified extracts of A. suum superoxide dismutase; (2) superoxide dismutase from host liver, and (3) purified extracts of superoxide dismutase from living A. suum incubated in the presence of these drugs. Thiabendazole compounds, with a documented effect against helminth parasite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…In contrast, the rest of the potential sites (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) are much smaller, exposed to solvent, and in many cases, well conserved respect to the human enzyme. In a first stage, the previously generated conformers for each ligand were scanned against all sites on the TsCu/Zn-SOD surface, using 15,000 poses of probe for each conformer.…”
Section: Compound Structurementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the rest of the potential sites (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) are much smaller, exposed to solvent, and in many cases, well conserved respect to the human enzyme. In a first stage, the previously generated conformers for each ligand were scanned against all sites on the TsCu/Zn-SOD surface, using 15,000 poses of probe for each conformer.…”
Section: Compound Structurementioning
confidence: 99%
“…As reported by some authors [9], albendazole inhibits microtubule formation in parasite by binding to b-tubulin, however, as shown by Sánchez-Moreno et al [17][18][19], this drug also inhibits SOD enzymes in helmints, but at high concentrations in the case of T. solium, as reported by us [20]. Gómez-Contreras et al [21] reported recently the synthesis of benzo[g]phthalazine derivatives which selectively inhibit Fe-SOD activity and growth of Trypanosoma cruzi.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of crystal field stabilization for the d 10 monovalent silver cation, coupled with its ability to tolerate a wide range of coordination geometries (with coordination numbers spanning 2-7), leads to considerable variation in the geometry and connectivity of the networks that can be formed when Ag(I) centers act as connectors [14,15]. Their various biological applications have also attracted attention [16].…”
Section: Introductionmentioning
confidence: 99%
“…Imidazole and its derivatives are very important from a biological point of view [8]; namely, benzimidazole as the 5,6-dimethyl derivative is present in vitamin B 12 and related biomolecules [9] and other benzimidazole compounds have found wide use as anthelmintic agents for both human and veterinary purposes [10]. In addition, it has been reported that several copper complexes with benzimidazole derivatives show inhibitory effects on helminth parasites [11]. Imidazole is also one of the most biologically important ligands.…”
Section: Introductionmentioning
confidence: 99%